2004
DOI: 10.1210/me.2004-0245
|View full text |Cite
|
Sign up to set email alerts
|

Coregulator Recruitment and Histone Modifications in Transcriptional Regulation by the Androgen Receptor

Abstract: We have used chromatin immunoprecipitation (ChIP) assay to follow transcription factor loading and monitor changes in covalent histone modifications associated with the prostate-specific antigen and kallikrein (KLK2) genes in response to androgen and antiandrogen in LNCaP cells. The dynamics of testosterone (T)-induced loading of androgen receptor (AR) onto the proximal promoters of the genes differed significantly from that onto the distal enhancers. Significantly more holo-AR was loaded onto the enhancers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 74 publications
13
126
1
3
Order By: Relevance
“…DHTinduced recruitment of AR to the AREIII was more pronounced than that to the AREI. This observation is in accordance with previous reports showing that more AR is recruited to the AREIII than to the AREI in response to androgen stimulation (Louie et al, 2003;Kang et al, 2004). For this reason, we decided to focus on AR recruitment to AREIII.…”
Section: Ser81 Phosphorylation Of the Arsupporting
confidence: 90%
“…DHTinduced recruitment of AR to the AREIII was more pronounced than that to the AREI. This observation is in accordance with previous reports showing that more AR is recruited to the AREIII than to the AREI in response to androgen stimulation (Louie et al, 2003;Kang et al, 2004). For this reason, we decided to focus on AR recruitment to AREIII.…”
Section: Ser81 Phosphorylation Of the Arsupporting
confidence: 90%
“…However, Kang et al, (2004) found that 200X more AR was loaded on to the enhancer compared to the promoter ARE of the PSA gene, but both promoter and enhancer ARE were needed for maximal activity. Conversely, more RNA polymerase II transcription factor was recruited to the promoter ARE.…”
Section: Androgen Receptor Signalling Pathwaymentioning
confidence: 98%
“…Conversely, more RNA polymerase II transcription factor was recruited to the promoter ARE. Differential histone acetylation modifications were noted between the promoter and enhancer ARE of PSA with the promoter ARE dependent on RNA polymerase II phosphorylation (Kang et al, 2004, Wang et al, 2005.…”
Section: Androgen Receptor Signalling Pathwaymentioning
confidence: 99%
“…Chromatin immunoprecipitation studies in LNCaP cells have shown that DHT stimulates the very rapid (within 15 min) recruitment of AR and coactivator proteins to endogenous androgen-regulated genes, including the PSA gene (36,37). Therefore, time course studies were done to assess whether Ser-81 phosphorylation was linked to chromatin recruitment of the endogenous AR in PCa cells.…”
Section: Cdk1mentioning
confidence: 99%